Using Natural Sciences for Cultural Expansion: The National Socialist Agenda for the Balkans - Zarifi, Maria (The Historical Review/La Revue Historique, 2008)
This article highlights the political merit natural sciences were awarded under the totalitarian regime of Nazi Germany and their propagandistic role in Hitler’s foreign policy agenda for the Balkans, a region which was expected to replace Germany’s colonies lost in World War I. It accounts further for the policies and strategies National Socialists used to exert cultural influence on the countries of South-East Europe, namely through a number of institutions with which natural sciences were in one way or another involved in order to promote German culture abroad. The promotion of the German language and, to a certain degree, the Nazi ideology was a precondition for familiarising the Balkan countries with German scientific achievements, which would pave the way for an economic and political infiltration in that region. Therefore, natural sciences, as part of the German intellect, acquired political and economic connotations hidden behind the euphemistic term of cultural policy, designed for this region of geopolitical importance. The article is based almost exclusively on unpublished German records.